Association between Tissue Polypeptide Specific Antigen and Vascular Endothelial Growth Factor in Colorectal Cancer Patients and their Relation with P53 Expression and Global DNA Methylation - Falih, Dalya; AL-Jumaily, Rakad (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Colorectal cancer is a high risk disease with rapidly progression medical problems and high mortality rate. Tissue polypeptide specific antigen can be classified as biomarker candidates in colorectal cancer and other kinds of cancer. Vascular endothelial-derived growth factor has a curial role in the formation of new blood vessels. DNA methylation may decrease invasiveness of cancer.Objectives: This study was designed to measure the potential role of some serological biomarkers in the progression of colorectal cancer as well as their relations to P53 expression, global 5-methylcytosine.Patients and Methods: This study involved of 60 patients with colorectal cancer who attended Oncology Teaching Hospital in Baghdad, Iraq and compared with 30 apparently healthy volunteers. All participants were checked for serological biomarker levels using an enzyme-linked immunosorbent assay. Also, DNA and RNA extracted and the levels of 5-methylcytosine and P53 expression were evaluated. The SPSS version 24.0 program was used for all statistical analysis done in this study.Results: The analysis of serological biomarker data has shown that the mean of tissue polypeptide specific antigen and vascular endothelial growth factor was significantly higher for patients with colorectal cancer, while it was lower for control subjects (356.4 ± 16.9, 139.75 ± 7.31) and (1127.82±65.41, 388.93±35.86), respectively. Also, a significant positive relation between tissue polypeptide specific antigen and vascular endothelial growth factor in the tumor area was significantly associated with control (P≤ 0.001). However, there was significant correlation in the levels of P53 expression and global DNA methylation between studied groups as well as tissue polypeptide specific antigen and vascular endothelial growth factor (P ≥ 0.05).Conclusion: The serological biomarkers include tissue polypeptide specific antigen and vascular endothelial growth factor and they play a critical role in the development of colorectal cancer. Serum vascular endothelial growth factor is useful in distinguishing colorectal cancer from healthy controls, whereas tissue polypeptide specific antigen is an independent prognostic factor for colorectal cancer proliferation.Received: Mar. 2023Accepted: Jun 2023Published: Oct.2023